E|Benchmark - A pioneering method for energy efficient process planning and assessment along the life cycle process - Kreitlein, Sven; Schwender, Sabrina; Rackow, Tobias; Franke, Jörg (Procedia CIRP, 2015)
This paper introduces a method for the assessment and evaluation of energy efficiency of the manufacturing processes in the production from the perspective of production planning. Production planning is an organizational entity within an enterprise and deals with the creation and provision of all production relevant documents and equipment in order to achieve maximum efficiency through a minimum of resources and effort. The tasks of production planning are evaluated by means of their relevance for an energy efficiency comparison. For this, evaluation criteria are determined that consider influences on the production processes and basic goals of production. This is necessary due to the fact that tasks of production planning cannot be evaluated directly via energy consumption and energy efficiency. This results in 12 tasks through which a high leverage effect for a more energy efficient production can be achieved. Another possibility for an energy efficiency evaluation is presented via the approach of minimal value calculation. The underlying concept is the comparison and evaluation of energy efficiency based on the ratio of the theoretically required energy consumption to the actual energy consumption. By linking the minimum value calculation to the production planning, a predetermination of the theoretical energy consumption - And thus an energy efficient planning - is possible. The resulting energy saving potentials extend over the entire life cycle of a process and enable savings of an increasing energy amount.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Energy efficiency; Process forward-planning; Sustainable manufacturing